Hubungan antar Hambatan Green Supply Chain Management (GSCM) pada Industri Kelapa Sawit di Indonesia - Rangga Primadasa; Dina Tauhida (Jurnal Optimasi Sistem Industri, 2020)
The palm oil industry as an important industry in Indonesia is demanded to conduct business in a sustainable way, including the implementation of green supply chain management (GSCM). However, in order to implement GSCM in the oil palm industry there are many barriers, but not yet comprehensively formulated what the barriers are and how to eliminate it. This study aims to identify barriers GSCM in the palm oil industry in Indonesia, to model the relationship between GSCM barriers and to classify any of it to the palm oil industry in Indonesia using the MICMAC approach. The interpretive structural modeling method was used in this study, where the stages began with a literature study to obtain GSCM indicators of the palm oil industry in Indonesia, then breakdown to get the barriers. The structural self-interaction matrix (SSIM) is then structured based on contextual relationships between obstacles by experts who have worked in the palm oil industry. Furthermore, SSIM is converted into a binary matrix. To get the level of each barrier, the level partitions stage is used to developing a chart and a model between the GSCM barriers in the palm oil industry in Indonesia. This research resulted in 15 GSCM barriers in the palm oil industry, then arranged into a 6-level model of GSCM barriers and divided into four clusters. The implication of this research is the addition of knowledge about GSCM especially the palm oil industry. While managerially giving direction on the strategy to eliminate GSCM barriers in the palm oil industry.